Hair line characteristics of young Kurdish males - M Yonis, Abdulsalam; Abduljaleel Kadhe , Ali; Sadeq Tauma, Ali; Mowffaq Ramzi, Ramzi (International Journal of Psychosocial Rehabilitation, 2020)
This is a descriptive cross sectional study of hair line characteristics conducted on 225 young Kurdish males aged 15-25 years old(mean=21), the purpose of this study is to define a model and characteristics of this age group’s hair line in terms of shape and level of the hair line, the shape was assessed by the presence or absence of the macro irregularities (widows peak 85%, lateral mound 90%) and the mean distances between them (widows peak to lateral mound Rt=4.25 ; Lt=4.18 cm, widows peak to temporal point Rt=97.8; Lt=7.8cm), the mean dimensions of the mid frontal macro irregularity (the widows peak height 1.49, width=2.73 cm), the height assessed by the mean distance from the inter eye brows point to the mid frontal point (5.65 cm), and the vertical distance from the temporal point to the lateral eye brow (Rt.=3.38cm, Lt=3.39cm), these measurements resulted in a rather low hair line and the shape was irregular and a wave like in (85%) with the presence of both the widow’s peak and lateral mounds, irregular with W or inverted V shape in (5%) with the presence of the lateral mounds only, and straight hair line in (10%) with the absence of both types of macro irregularities.